Trepanaciones históricas y prehistóricas en Venezuela - Gómez-González, Drs. Jaime; Briceño-Iragorry, Leopoldo (Gaceta Médica de Caracas, 2020)
Los autores hacen el informe preliminar del primer cráneo trepanado en la época precolombina en Venezuela.Hacen referencia a las primeras operaciones craneanas publicadas en Venezuela en los siglos XVIII yXIX por insignes cirujanos precursores de la cirugía neurológica. También se citan otras intervenciones practicadas en Hispanoamérica en los siglos XVI y XVII. SUMMARY Authors present the preliminary report on the first trepanned skull in the pre-Columbian period in Venezuela.References are made on the first skull interventionspublished in Venezuela during the XVIII and XIXcenturies by distinguished precursors surgeons of theneurologic surgery. Other interventions performed duringthe XVI and XVII centuries in Latinoamerica are alsoquoted.